Innovation and Characterization of Zeolite from Matoa Fruit for Adsorption of Heavy Metals Cu(II) - Rahman, Ainul Alim; Fadlil, Firmanullah; Tuheteru, Hajirum; Halijah, Siti (Politeknik Negeri Malang, 2025)
Matoa fruit is abundant in Papua and has not been optimally utilised. Matoa fruit consists of ash approximately 3.74%. The high ash and silica content make it highly suitable as a raw material for zeolite production. Zeolite can be used as a zeolite material to adsorb heavy metal Cu(II). Heavy metal pollution continues to increase with industrial growth. Heavy metals can harm human health. Innovation must continue addressing heavy metal pollution, such as Cu(II), to produce more efficient, cost-effective, and environmentally friendly technologies. This study aims to determine the ability of matoa fruit zeolite to adsorb heavy metal Cu(II). The characterization of zeolite was done using XRD (X-Ray Diffraction) and SEM (Scanning Electron Microscope). The synthesis process involved preparing sodium aluminate and sodium silicate solutions, followed by controlled crystallisation at 105°C for 24 hours. The zeolites were tested for adsorption with the independent variable being zeolite mass, while the dependent variables were contact time of 48 hours and stirring time of 4 hours. SEM analysis confirmed the cubic morphological characteristics of matoa fruit zeolite, classifying the product as matoa fruit zeolite. The main findings of the study showed that matoa fruit zeolite can reduce Cu metal levels in sewage-polluted water with 88.85% adsorption at 0.5 g in 50 ml of test solution.